Design Strategies for Working Space to Reduce The Behavior of Stress and Preserve The Heritage Values of Banjarbaru City Hall Building - Adithea Syahputra Perdana; Asri Dinapradipta; Fransciscus Teddy Badai Samodra (Jurnal Teknik ITS, 2019)
Designing government working space is proposed to solve the productivity issues among the workers inside the city hall office building of Banjarbaru city in South Borneo. This caused either by their work span inside the office and the style of working cubical or the interior element which has colonialsm values. The design of the building case is using the colonial style which is this building’s materials have color dominated with white colour and the architecture elements are containing a heritage value. Therefore, in this paper discuss the literature review to make a design srtategies for working space inside the office with building heritage’s values that suitable to maximizing the productivity of the workers by involving them in the process of design in advance, for instance, the design process will use a participatory design paradigm that will be reviewed before applicate it in the Banjarbaru government office design proposal. From those theories can be concluded that field area like shape, colors, and perception of space which related to an interior element can be controlled to maximizing the productivity and preserving the values of building heritage.